Síntese e caracterização de vanadato de prata decorado com hidroxiapatita - Silva, Jussara Soares da (2018)
The continued need for improved technological devices makes the development of advanced nanostructured materials urgently. Hydroxyapatite [HA, Ca10(PO4)6(OH)2] is a biocompatible material well known for its optical properties that makes HA nanoparticles ideal for bioimaging procedures and for light emitting diodes (LEDs). On the other hand, silver vanadate [AV, AgVO3] has interesting bactericidal, photocatalytic and optical properties. The association of HA and AV may result in a superior material with combined properties, or even enhanced by synergistic effects. The objective of this study was the preparation of silver vanadate powders in the alpha phase decorated with hydroxyapatite (AV:HA) with different molar ratios by the chemical precipitation method in aqueous solution. The AV:HA samples were characterized by X-ray diffraction (XRD), ultraviolet-visible (UV-Vis), Fourier transform infrared (FTIR) and RAMAN spectroscopies. They were also analyzed by scanning electron microscopy (SEM) and scanning electron microscopy transmission (TEM). Structural characterization by XRD confirmed the presence of single HA and AV phases in all samples. All typical modes of both materials were observed by vibrational spectroscopies. It was possible to observe the formation of materials composed of AV microrods and HA nanorods, through the morphological analyzes from the microscopic techniques. The UV-Vis absorption measurements provided the Egap values of the decorated samples that were assimilated to that of the pure vanadate. The photoluminescence (FL) properties at room temperature were evaluated by the study of their emission spectra. Broad band emissions were obtained within the region of visible light in the electromagnetic spectrum (regions corresponding to blue and red color) obtaining even white light emission, according to the different AV: HA molar ratios. These results demonstrate the possibility of adjustable emission colors in the AV: HA system, making it interesting for future applications in optical devices with different FL emissions.